PENGGEROMBOLAN KECAMATAN DI PROVINSI JAWA BARAT BERDASARKAN AKSES PENDIDIKAN MENENGAH ATAS (SMA-SEDERAJAT) DENGAN K-PROTOTYPES - Sofia Octaviana; Ahmad Syauqi; Anwar Fitrianto; Erfiani Erfiani; Alfa Nugraha Pradana (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2024)
Education is an important element for the Indonesian nation and must be felt by all citizens. The availability of educational facilities is important for the realization of overall educational equality for the Indonesian people. The aim of this research is to group sub-districts in West Java Province according to their level of access to Senior High School (SHS-equivalent). The data included in this study comprises both numerical and categorical variables, which were obtained from the 2021 Village Potential Data Collection (PODES) conducted by the Central Statistics Agency. A cluster analysis method that can be used to group objects based on numerical and categorical data is K-Prototypes. The results of the grouping divide the data into 2 groups, where the first group has the characteristics of an urban subdistrict, the topographic area is plain, access to the nearest high school is very easy, and has an average number of high school and equivalent schools of 22 schools per subdistrict, and has an average distance to the nearest high school of 1,86 km. Meanwhile, the second group has the characteristics of subdistricts with rural areas, topography in the form of slopes, easy access to the nearest high school, and has an average number of high schools of 7 per subdistrict, and the average distance to the nearest high school is 4,06 km. The second group is sub-districts that need to be given special attention because they have relatively fewer high schools and the distance to the nearest high school is further